Implementasi Kurikulum Pendidikan Agama Islam di MA Nihayatul Amal Rawamerta Karawang - Febrian, Yani; Utami, Ayu Endah; Rijalallah, Rizky; Arifudin, Yadi Fahmi (Universitas Negeri Padang, 2024)
Education is the most important foundation in the formation of quality individuals and society. The concept that education is a conscious and planned effort highlights the importance of careful planning and deep awareness in every aspect of learning. The curriculum is one of the most important parts in the world of education, because the curriculum is used by educational experts, especially teachers to develop a more innovative educational process and can achieve the expected educational goals. This study aims to determine the Islamic religious education curriculum implemented at MA Nihayatul Amal Rawamerta Karawang. In collecting data, the method used is through a descriptive qualitative approach, namely by means of observation, interviews, and documentation. The conclusion of the research shows that at MA Nihayatul Rawamerta there are two curricula used, namely the 2013 curriculum for grades 11 and 12, and the independent curriculum for grade 10.